Visiting the labyrinth of religious transformation - Johnson‐Miller *, Beverly (Journal of beliefs and values, 2005)
Understanding the complexity of religious transformation requires empirical contextualized research on the continuous dynamic relationship between formation and transformation. Narrative study in context unveils the implicit meaning of phenomena made explicit in stories. This article, through a biographical case study of a Mennonite woman’s religious journey, explores the complex nature of religious transformation with particular attention to intricate interplay of factors. Critical insights regarding the inseparable relationship between formation and transformation are made clear through an in‐depth examination of lived experience, yielding implications for religious education.